Examining the pressure of the program on the performance of human resources working on the site of construction projects - Yasaman Hajnorouzi; Hashem Shariatmadar (مهندسی و مدیریت ساخت)
Schedule pressure is caused by various factors in construction projects, and the role of human resources performance in improving or increasing this pressure is very important and decisive. In this article, the structural equation modeling method was used to investigate the effect of program pressure on the performance of human resources working at the site of construction projects. In order to achieve this main goal, the effective variables were first identified and referenced through the research background and experts' opinion in the initial questionnaire. Also, the reliability and validity of the questionnaire created by the researcher were checked and confirmed according to Cronbach's alpha coefficient and confirmatory factor analysis. In the next stage, the theoretical model of the research is drawn and after collecting information in the case study of the research (two Ofoq engineering companies in Tehran and the Energy Industry Design and Engineering Company (EIED), civil and architecture department), a structural model for the relationship between the latent variables with each other and also The relationship between obvious and latent variables was drawn and then validated. The findings of the research were drawn in the form of 6 latent variables, schedule pressure, human resources performance, safety atmosphere and culture, training and awareness of human resources, rework and managers' decisions.As a result, indirect and total relationships as well as correlation between research hypotheses were compared and analyzed. According to the findings, the total and indirect relationships of the structural equation model have many differences with the results of the research hypotheses that have been obtained through the bootstrap test.